(untitled) (Journal of Scientific Research, 2011)
Synthesis of two methoxy bridged bis(silylene) complexes (CpMe4)W(CO)2 (Et2Si)••OMe••(SiMe2)(3) and (CpMe)W(CO)2 (Et2Si)••OMe••(SiMe2)(4) have been synthesized. Both the compounds contain chiral tungsten center and formed via oxidative addition of an Si-H bond to a coordinatively unsaturated metal center. The complexes were characterized by 1H, 13C, 29Si NMR, IR and elemental analysis. A plausible mechanism of formation is also suggested. Keywords: Coordinatively unsaturated; Chiral tungsten; Oxidative addition. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.7890 J. Sci. Res. 4 (1), 109-118 (2012)